1996
DOI: 10.1034/j.1600-0889.1996.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

The elemental signature of transported Asian dust at Mauna Loa observatory

Abstract: Dust storms in Asia's interior deserts loft immense quantities of continental crust that are blown over the North Pacific Ocean every year. The transported mineral aerosol is first lofted and then experiences mixing and fallout during the transport. Its elemental signature is no longer that of bulk soil. The concentration for many elements is greater in transported crust compared to bulk soil due to a difference in mineralogy of the small crustal particle. Small particles are defined as those below 100 μm in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 0 publications
10
21
0
Order By: Relevance
“…Whereas the high percentage soil events with relatively constant (nss-Ca/Al) ratios around unity were more likely to be due to long-range windblown soils transported from the Chinese mainland ; Holmes and Zoller, , 1997]. Average coarse dust [Al/Ca] ratios of (1.3 ± 1.2) measured by Holmes and Zoller [1996] for Asia dust over the Mauna Loa observatory on Hawaii are also consistent with this argument. Consideration of back trajectories and meteorological data would help resolve this problem and will be considered further in a future publication when we look in detail at source fingerprinting, source apportionment and transport using this data set.…”
Section: Fine Soil Estimatesmentioning
confidence: 62%
See 1 more Smart Citation
“…Whereas the high percentage soil events with relatively constant (nss-Ca/Al) ratios around unity were more likely to be due to long-range windblown soils transported from the Chinese mainland ; Holmes and Zoller, , 1997]. Average coarse dust [Al/Ca] ratios of (1.3 ± 1.2) measured by Holmes and Zoller [1996] for Asia dust over the Mauna Loa observatory on Hawaii are also consistent with this argument. Consideration of back trajectories and meteorological data would help resolve this problem and will be considered further in a future publication when we look in detail at source fingerprinting, source apportionment and transport using this data set.…”
Section: Fine Soil Estimatesmentioning
confidence: 62%
“…[33] Soil has previously been identified as a significant component of the Asian aerosol in our study region Chang et al, 1996;Holmes and Zoller, 1996;Kim et al, 1998;Cheng et al, 2000;Hien et al, 2002;Jaffe et al, 1999]. Kim et al [2003] found that during the spring of 2001, Asian dust events were the prominent sources of major crustal components in the fine fraction of particulate matter.…”
Section: Fine Soil Estimatesmentioning
confidence: 66%
“…One would expect if this component were due to the different mineralogy associated with small crustal mineral particles usually observed to undergo long-range transport [Shaltz and Rahn, 1982], that it would be more consistent and less sporadic. It would also be modeled by an Asian dust signature, which it is not [Holmes and Zoller, 1996]. Many of the 500 hPa back trajectories cross over various industrial or urban regions including parts of Europe and Japan [Harris and Kahl, 1990;Harris et al, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…[24] To verify that our method correctly identified Asian dust independent of some artifact in the IMPROVE record, we compared mean and standard deviation for Aluminumelemental ratios for our data and the Mauna Loa Asian dust characterization reported by Holmes and Zoller [1996]. The previously published ratios are for the Asian subset of a 12-year record of weekly samples taken from 1970 through 1991 (500+ samples, 250+ identified as Asian dust), analyzed by neutron activation.…”
Section: Testing the Historical Record At Mauna Loamentioning
confidence: 99%